ANALISIS KUALITAS AIR SUNGAI TANOYAN DI KOTA KOTAMOBAGU PROVINSI SULAWESI UTARA - Abidjulu, Jemmy (Sam Ratulangi University, 2008)
A research has been done about the quality of water from Tonayan river in Kotamobagu city Province ofNorth Sulawesi based on its physics and chemical parameter. The sample was taken on three spot withduplo methods. The first sample was undertaken on the upperstream at Tanoyan village, second wasundertaken on the downstream at Mopait village and the third was undertaken at Kopandakan village.Analysis of water using Turbiditimetry, pH-metri, EDTA, and Spectrophotometer methods. The resultthat had been obtained was compared with the standart of pure water class II based on the governmentrules No.82 year 2001. Based on the research result, the quality of river water at the three spot are: notaste, no flavor, turbidymetry ( 3,1-9 NTU), pH (6,5-7,9), saturated (440-560 mg/1), chloride (0,02-21,02mg/L), ferrum (<0,01-0,036 mg/L), mangannese (0,02-0,071 mg/L), nitrat (<0,5 mg/L), seng (0,02-0,215mg/L), cyanide (0,11-0,01 mg/L), dan sulphat (2-71 mg/L). This research conclude that water inTonayan river Kotamobagu city Province of North Sulawesi for all parameters are in standart quality,accept saturated at first spot and zinc at the third spotÂ Keywords: Quality, water, river, physics parameter, chemical parameter